1 John 3.12, Early Judaism and the Greek Life of Adam and Eve - Levison, John R. (Journal for the study of the New Testament, 2020)
The seemingly sudden introduction of an allusion to Cain and Abel in 1 Jn 3.12 is puzzling. To explain this apparent intrusion, select scholars have turned to early Jewish interpretations of Gen. 4. The purpose of this study is to provide further grist for this mill. Beginning with an appraisal of the role Jewish texts play in the analyses of Ernst Lohmeyer, Raymond Brown and Judith Lieu, it continues with a detailed study of an ancient text that has been neglected in the interpretation of 1 Jn 3.12, the Greek Life of Adam and Eve (GLAE). A consideration of key features in the story of Cain and Abel in GLAE strengthens the possibility that 1 Jn 3.12 was part and parcel of an interpretive milieu that sharpened the divide between righteous and evil, between murderer and martyr.